Assessment of enzyme immunoassay versus radioimmunoassay for detection of Legionella pneumophila serogroup 1 antigen in frozen urine specimens. - Chang, F Y (1996)
An enzyme immunoassay (EIA) was compared with a radioimmunoassay (RIA) for detection of Legionella pneumophila serogroup 1 antigen in 37 frozen urine samples. Among 18 samples positive by the RIA at the time of collection, 50% (9 of 18) of stored specimens retained positivity when retested by the RIA whereas 78% (14 of 18) of stored specimens retained positivity when retested by the EIA (P < 0.02). A false-negative result occurred after storage for 5 months or less if the original RIA result showed weak positivity.